Cultural Capital: impact on students' access to higher education and their academic performance (Research, Society and Development, 2020)
In elaborating the concept of Cultural Capital, Pierre Bourdieu chose a different way of interpreting school and education, taking into account the association between students' learning and their social origin. It was found that there are elements characteristic of the cultural accumulation that is transmitted through informal education, especially in the family space, which impact the performance of students. Thus, the objective of this work was to identify the impact of Cultural Capital on students' access to Higher Education and on their academic performance, through the reading of texts produced from research already carried out. To make this study possible, steps were taken in the search for specialized education journals. It was carried out in a consolidated digital database: CAPES journals. Six original articles, which met the selection and exclusion criteria, published between 2009 and 2017, were retrieved from the consulted database. From the objectives and results of the articles read, the following categories of analysis of the publications were considered: Cultural Capital and access to Higher Education; Cultural Capital and academic performance. The literature demonstrated the existence of a significant relationship between the student's entry to higher education level and his her learning, with his her characteristics and that of his her family, which refers to Cultural Capital.